PWE-117 Prevalence of Falls in the Uk PBC Population. (4th June 2013) - Griffiths, L; Newton, J; Jones, D
Abstract : Introduction: Previous studies have documented the prevalence of falls in PBC in a geographical area but there is no published data on the prevalence of falls in a national UK PBC cohort. Prevalence of falls was reported as 70% in the Newcastle-upon-Tyne cohort. Risk factors for falls are known to be prevalent in people with PBC, particularly autonomic dysfunction and lower limb muscle weakness and combined with the high prevalence of osteoporosis this carries a significant risk to the patient from falls and falls related injuries with the associated healthcare and financial implications. This study aimed to assess the prevalence of falls in the National PBC cohort as well as associated falls related injuries and related hospital admissions. We also explored the relationship between falls and autonomic symptoms. Methods: Symptom assessment tools were completed by patients as part of the UKPBC genetics study. Information about falls and associated injuries was collected using a standardised data capture tool and autonomic symptoms were quantified using the Orthostatic Grading Score. Results: Data was collected on 2328 patients with PBC from all around the UK. 862 (37%) of PBC patients had fallen, 118 (8%) were current fallers (one fall within the past year) and 414 (17.7%) were recurrent fallers (more than one fall in the past year). 35% of patients attended A&E following their fall with 9.7% of fallers requiring admission as a consequence of their fall and 24% of PBC patients who fell sustained a fracture. Fallers were significantly more likely to be diabetic (diabetes present in 5.7% of non-fallers and 12.2% of fallers, p < 0.0001) and more likely to be taking cardioactive medication (29% in non-fallers and 71% in fallers, p < 0.0001). Autonomic symptoms were significantly more prevalent in those PBC patients with recurrent falls (mean OGS 5.44, SD 4.15) compared to non-fallers (mean OGS 2.38, SD 2.13)and infrequent fallers (mean OGS 3.2, SD 3.36) p < 0.0001. Conclusion: A significant percentage of patients with PBC are falling, sustaining fractures and being admitted to hospital following a fall. This has huge implications for patients with PBC in terms of morbidity, mortality and quality of life. The high prevalence of autonomic symptoms in the population that fall demonstrate the importance of considering this symptom in all PBC patients as there are a number of interventions that can be implemented. Patients that fall often have more than one risk factor and this study demonstrated this as autonomic symptoms, diabetes and the presence of cardioactive medications were all more common in the cohort of fallers therefore all patients with PBC need a careful assessment for the presence of falls risk factors and a multidisciplinary approach to reduce the risk of falls. Disclosure of Interest: None Declared.